2011
DOI: 10.1128/jb.05429-11
|View full text |Cite
|
Sign up to set email alerts
|

Role for Escherichia coli YidD in Membrane Protein Insertion

Abstract: YidC has an essential but poorly defined function in membrane protein insertion and folding in bacteria. The yidC gene is located in a gene cluster that is highly conserved in Gram-negative bacteria, the gene order being rpmH, rnpA, yidD, yidC, and trmE. Here, we show that Escherichia coli yidD, which overlaps with rnpA and is only 2 bp upstream of yidC, is expressed and localizes to the inner membrane, probably through an amphipathic helix. Inactivation of yidD had no discernible effect on cell growth and via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…We generated a strain of E. coli in which both YidC and SecF can be depleted by placing chromosomal yidC and chromosomal secDF under the control of arabinose promoters. Immediately upstream of and cotranscribed with yidC is the small nonessential open reading frame yidD, which encodes a factor that participates in membrane protein insertion (33). Immediately upstream of and cotranscribed with secF are yajC and secD, which encode accessory proteins to the Sec translocon.…”
Section: Resultsmentioning
confidence: 99%
“…We generated a strain of E. coli in which both YidC and SecF can be depleted by placing chromosomal yidC and chromosomal secDF under the control of arabinose promoters. Immediately upstream of and cotranscribed with yidC is the small nonessential open reading frame yidD, which encodes a factor that participates in membrane protein insertion (33). Immediately upstream of and cotranscribed with secF are yajC and secD, which encode accessory proteins to the Sec translocon.…”
Section: Resultsmentioning
confidence: 99%
“…Seq2Ref provided more information by detecting (e-value 8.0e-49; 90% identity; reciprocal best hit) the experimentally studied protein YidD from E. coli (gi|67476547), which is identical to the NCBI nr database representative protein (gi|16767126) from Salmonella enterica . This orthology is reinforced by the common conserved genomic context [23] (Additional file 2: Table S2) and the CLANS [24] protein similarity network, in which E. coli YidD and C. turicensis hlyA cluster tightly together among their homologs (Additional file 3: Figure S1). The reference [23] associated with E. coli YidD detected by our server suggests that YidD assists YidC, the protein insertase, in insertion of inner membrane proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This orthology is reinforced by the common conserved genomic context [23] (Additional file 2: Table S2) and the CLANS [24] protein similarity network, in which E. coli YidD and C. turicensis hlyA cluster tightly together among their homologs (Additional file 3: Figure S1). The reference [23] associated with E. coli YidD detected by our server suggests that YidD assists YidC, the protein insertase, in insertion of inner membrane proteins. As a confident ortholog of E. coli YidD, the hlyA gene from C. turicensis very likely shares the same function.…”
Section: Resultsmentioning
confidence: 99%
“…It would be of interest to determine whether these proteins also interact physically to confirm experimentally the presumed role of YidC in membrane protein quality control. The overexpression of the regulators of the glutamate-dependent acid resistance system, GadX and GadY, in an E. coli YidC depletion strain restores the ability to generate a proton motive force and leads to an increased membrane sequestering of the chaperone GroEL (Yu et al , 2011b ). It was suggested that GroEL replaces YidC function and keeps newly synthesized membrane proteins in an insertion-competent conformation.…”
Section: Membrane Quality Controlmentioning
confidence: 99%